Subtype-selectivity of metal-dependent methionine aminopeptidase inhibitors - Altmeyer, Markus; Marschner, Aline; Schiffmann, Rolf; Klein, Christian D. (Bioorganic & medicinal chemistry letters, 2010)
Inhibitors of methionine aminopeptidases (MetAPs) are treatment options for various pathological conditions. Several inhibitor classes have been described previously, but only few data on the subtype selectivity, which is of crucial importance for these enzymes, is available. We present a systematic study on the subtype- and species-selectivity of MetAP inhibitors that require the binding of an auxiliary metal ion. This includes, in particular, compounds based on the benzimidazole pharmacophore, but also hydroxyquinoline and picolinic acid derivatives. Our data indicates that a significant degree of selectivity can be attained with metal-dependent MetAP inhibitors.
Gesehen am 22.11.2022